Sosialisasi Tanda Batas Tanah dan Pendaftaran Tanah Sistematik Lengkap Di Kelurahan Gedung Meneng Baru Kecamatan Rajabasa Kota Bandar Lampung - Sumarja, FX; Akib, Muhammad; Tisnanta, HS; Triono, Agus (FT Universitas Lampung, 2024)
There are landowners in Gedungmeneng Baru Village, Rajabasa Subdistrict, Bandarlampung City who do not install land boundary signs according to regulations, both in terms of shape, size and material. The absence of boundary marks or non compliance with land boundary mark rules can trigger disputes. This can happen because, firstly, the community is not aware of the provisions governing the shape and size of land boundary marks. Secondly, even if they are aware, they do not understand the provisions. Thirdly, even if they understand, they do not care about the situation around them regarding the installation of land boundary markers. This activity aims to increase the understanding of land rights holders about their rights and obligations as landowners, related to land boundary markings, and increase residents' understanding of the Government's program on Complete Systematic Land Registration (PTSL). The results of the activity showed an increase in legal knowledge and understanding, which initially only obtained an average score of 55.20 increased to an average of 74.50. The understanding of the shape and size of land boundary marks also increased. Thus residents have an understanding of the rights and obligations as landowners and good neighbors related to land boundary signs) and have a caring attitude towards the surrounding environment, to prevent land disputes by installing land boundary signs and trying to register land.